Impact of Flexible Work Environments on Employee Performance: Mediating Roles of Stress and Work-Life Balance - Mandalahi, Santa Hosiana; Damayanti, Shinta; Prasanti, Tiara Afifah; Maharani, Anita (Yayasan Sinergi Kawula Muda, 2024)
Employee performance is crucial for the success of organizations, influenced by various factors such as work stress and work-life balance. This study focuses on the impact of flexible work environments on employee performance, with work stress and work-life balance as mediating factors. The main aim of this research is to investigate the relationship between flexible work environments, work stress, work-life balance, and employee performance. The research utilized a quantitative approach with a sample of employees from various industries. Data was collected through questionnaires assessing perceptions of flexible work environments, work stress, work-life balance, and employee performance. Statistical analysis, including regression analysis and mediation analysis, was conducted to examine the relationships between the variables. The findings indicate that a flexible work environment has a positive impact on work stress and work-life balance, which, in turn, leads to improved employee performance. Regression analysis revealed significant relationships between these variables, highlighting the importance of flexibility in enhancing employee well-being and performance. This research demonstrates the significance of flexible work environments in promoting work-life balance and reducing work stress, ultimately enhancing employee performance. Organizations should consider implementing flexible work policies to support employee well-being and productivity. These findings have implications for human resource management practices and organizational policies aimed at creating a conducive work environment for employees.